The Influence of Entrepreneurial Ecosystem on SMEs Industry in Malaysia - Aziz, Zarith Delaila Abd; Hussein, Norashikin; Rahman, Nor Azian Abdul; Omar, Muhamad Khalil (Advances in Social Sciences Research Journal, 2022)
The rise of Small Medium Enterprise (SMEs) businesses leads to the dynamic and competitive environment. To excel in the market, companies have spent a substantial amount of money, time and resources by designing right strategies to sustain. However, this SMEs businesses faces few challenges such as small capital investment, short of talent, limited access to infrastructure and support mechanism. Despite the government’s several institutional and policy support for enhancing the capacity of this Small Medium scale enterprises, the results have fallen short of expectations. Given the increased demand for Small Medium Enterprise’s products, creating a viable entrepreneurial ecosystem model for SMEs in Malaysia is critical. This is because the entrepreneurial ecosystem is a system of interrelated components that influence the speed and ability with which entrepreneurs, particularly SMEs can create and scale new ventures in a sustainable manner. As a result, this study seeks (1) to analyse the demographic profile of Malaysian small and medium enterprise and (2), determine the extent at which entrepreneurial ecosystem affect the Small Medium Enterprise in Malaysia. This study is important to investors, the ministry, the government, academics and even business owners because it provides a comprehensive model for understanding the SMEs entrepreneurial processes and how ecosystems emerge, change and influence entrepreneurship activities.